Millennial Generation's Understanding of the Meaning of Kafa’ah : An Analysis in the City of Banda Aceh - Hanapi, Agustin; Najmi, Khairul (Universitas Islam Negeri Sumatera Utara, 2024)
Islam shows great concern for the welfare of the family. In forming a family, prior to marriage, the prospective husband and wife should know each other's partners. Harmony and balance between partners is needed in navigating the household ark. This can be done from the apprenticeship stage, which is when a person determines who is worthy of being his life companion. Harmony and balance in Islam is known as kufu 'or kafa'ah. In this modern era, it is not uncommon for us to find domestic problems that are caused by a striking difference between the two various things, both in terms of religion, race, social status, and so on. The criteria for kufu’ in Islam basically only include the factors of wealth, heredity, beauty and religion. However, over time, this concept has developed into several factors such as age, occupation, education, and even religious organizations. Unbalanced couples often lead to disputes between the two. Meanwhile, a balanced couples will greatly assist the socialization process towards family happiness, namely the sakinah, mawaddah and rahmah families.